2016
DOI: 10.18178/joaat.3.1.10-14
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Myrtus Communis Oil Extract on Growth Performance and Immune Responses in Ross and Cobb Strain Broilers

Abstract: This experiment was carried out to compare the performance and immune responses in Ross and Cobb broilers fed diets containing Myrtus communis oil extract (MCE). A total of 224 one-d-old broiler chickens randomly allocated to each of the 4 treatment groups, each with 4 replicate pens of 14 chicks. The experimental diets included two treatments for Ross straincontrol (RC) and the diet contain 500mg/Kg MCE (RM)-and two treatments for Cobb strain-control (CC) and the diet contain 500mg/Kg MCE (CM). The performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The significantly lower serum glucose level in the MPEL-50 and MPER-50 myrtle groups in this study may be explained by the hypoglycemic effect of myricetin. Similarly, Aljebory [ 11 ] and Saei et al [ 28 ] reported that myrtle extract, given at a dose of 500 mg/kg, reduced blood glucose levels in rabbits and broilers, respectively. Various in vitro and in vivo studies have revealed that myricetin possesses the ability to alter the immune response or the functioning of the immune system by stimulating antibody formation.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The significantly lower serum glucose level in the MPEL-50 and MPER-50 myrtle groups in this study may be explained by the hypoglycemic effect of myricetin. Similarly, Aljebory [ 11 ] and Saei et al [ 28 ] reported that myrtle extract, given at a dose of 500 mg/kg, reduced blood glucose levels in rabbits and broilers, respectively. Various in vitro and in vivo studies have revealed that myricetin possesses the ability to alter the immune response or the functioning of the immune system by stimulating antibody formation.…”
Section: Resultsmentioning
confidence: 94%
“…Clinical and experimental studies have demonstrated its antioxidative, anticancer, antioxidant, antibacterial, antifungal, hepatoprotective, anti-diabetic, antiviral properties, as well as neuroprotective activity [ 8 , 9 ]. In recent years, the oils and extracts of the myrtle plant have been utilized to enhance performance in broilers [ 10 , 11 ], laying hens [ 12 ], rabbits [ 13 ] and rats [ 14 , 15 ]. Additionally, it has been employed as a chemotherapeutic agent in quails [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, especially on the 33rd day of the study, it was determined that the body weight value of the quails in the M and MLPS groups was significantly lower than the control and LPS group quails (P<0.05). However, it was reported that the addition of murt oil to Japanese quail feed (1000 mg/kg/day, Biricik et al 2012) and broiler feed (500 mg/kg, Sadeghi et al 2013;Goudarzi et al 2016) had a positive effect as a potential growth promoter. Animal performance characteristics and the dose difference of the herbal antioxidant added to the basal diet can be expressed as an important reason for the differences in the study results.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Biricik et al (2012), Sadeghi et al (2013) and Salehifar et al (2017) reported an improvement in feed efficiency of quail and chicks fed with murt oil added the diet. Similarly, Goudarzi et al (2016) stated that the addition of 500 mg/kg murt oil extract to the diet reduced feed intake and improved feed conversion ratio of Ross and Cobb broiler chickens.…”
Section: Discussionmentioning
confidence: 99%